Metode Istinbath dalam Konsep Kepemimpinan Politik dalam Islam - Muhammad Rezky; Ibnu Afif; Kurniati Kurniati (CV. ITTC INDONESIA, 2026)
This study discusses the method of istinbath in the concept of Islamic political leadership and its relevance to the development of modern politics in Indonesia. Istinbath is understood as a process of deriving Islamic law from the Qur’an, hadith, ijma’, and qiyas in order to formulate leadership principles that are in accordance with Islamic values and societal needs. This research employs a qualitative approach with a library research method by examining primary and secondary sources, including fiqh siyasah books, scientific journals, and Islamic legal literature related to Islamic political leadership. Data analysis was conducted descriptively and analytically using normative, historical, and contextual approaches. The results show that the istinbath method plays an important role in shaping the concept of Islamic political leadership based on trustworthiness, justice, deliberation, and public welfare. In addition, the implementation of istinbath contributes to the creation of a democratic, participatory, and socially responsive system of government. The values of maqashid al-shari’ah also serve as the foundation for adapting Islamic leadership principles to contemporary political challenges. Therefore, the istinbath method is capable of presenting an adaptive, humane, and relevant concept of Islamic political leadership within the modern governmental system in Indonesia.